Parameters Cp and Ct in Snyder Synthetic Unit Hydrograph Due to Land Use Changes in Napel Sub-watershed, Bengawan Watershed - Barid, Burhan; Ichsan, Samina W. (ASTONJADRO, 2024)
The parameters Cp and Ct depend on the characteristics and slope of the watershed. Watershed characteristics include types of land use that are always dynamic over time. The slope of the watershed affects the smoothness and velocity of runoff flow. The development of an area will cause changes in land use which tend to become more impermeable, of course also affecting the smoothness and speed of runoff flow. This of course results in changes in Cp and Ct in a watershed. Changes in land use in the Napel watershed within 7 years starting from 2015 to 2021 have decreased in areas of jungle forest and other water catchment areas. This research was conducted to determine the influence of land use change on peak discharge and Cp and Ct parameters. The method used is the Snyder Synthetic Unit Hydrograph, which has been tested for suitability against the Measured Unit Hydrograph with validation results included in the very strong correlation category. The Ct value used in 2015 was 1.65 and in 2021 it was 0.78 while the Cp value used in 2015 was 1.4 and in 2021 it was 1.1. The results of the analysis using the Snyder method produced a discharge of 417.882 m3/s in 2015 and 619.52 m3/s in 2021. The resulting discharge shows a significant increase.